TEKNIK IMUNOHISTOKIMIA SEBAGAI PENDETEKSI ANTIGEN SPESIFIK PENYAKIT INFEKSI - Yani Rahayu; Elza Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
Infections may be caused by bacteria, viruses, fungi, and parasites. The diagnosis can be established on the basis of signs and symptoms, should be representative of the disease process, and should be obtainal before drug administration. Diagnosis may be added by different techniques such as investigation on microscopic examination, enzymatic activity, immunoassays, serodiagnosis and genetic probes. The recently applied methods of immunohistochemistry, immunofluorescence and immunoperoxidase staining, can detect specific microbial antigens. Principle of the immunofluorescence technique is recognition of specific antibody-antigen reaction and its visualization by labeling a chromogenic substrate. The immunoenzyme techniques require the attachment of an enzyme to a specific antibody. The antibody-antigen complex can be recognized by an enzyme label (peroxidase), resulting in a coloured product after reaction with a specific substrate and chromogenic substrate. These techniques are histologically used for visualization tissue specimen labeling, and to detect localization of antigen.